2009
DOI: 10.1142/s0217979209049772
|View full text |Cite
|
Sign up to set email alerts
|

EXPERIMENTAL OBSERVATIONS OF DISK-SHAPED PATTERNS IN Fe FILMS SPUTTERING DEPOSITED ON SILICONE OIL SURFACES

Abstract: We report the experimental observations of large spatially disk-shaped patterns in an iron (Fe) film system deposited on silicone oil surfaces by a DC-magnetron sputtering method. These disk patterns form spontaneously during deposition and grow successively in vacuum condition after deposition. Their nucleation, growth and evolution are strongly dependent on the sputtering power, deposition period and growth time. The experiment indicates that they may result from the spontaneous organization and gathering of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…The first attempt to coat liquids was made by Ye et al, who successfully deposited continuous metallic films on silicone oil by RF magnetron sputtering and investigated the nucleation and growth mechanisms taking place during film formation [ 1 , 2 , 3 ]. Other groups followed this approach using different kinds of liquid substrate materials, such as silicone oils, ionic liquids and vegetable oils, to synthesize metal films and nanoparticles made of gold, silver, titanium, aluminum, iron, nickel and copper via sputtering and thermal evaporation processes [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Besides, the growth of crystals from different aromatic hydrocarbons, zinc, copper and gold on silicone oil and ionic liquids by vapor phase deposition was studied [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first attempt to coat liquids was made by Ye et al, who successfully deposited continuous metallic films on silicone oil by RF magnetron sputtering and investigated the nucleation and growth mechanisms taking place during film formation [ 1 , 2 , 3 ]. Other groups followed this approach using different kinds of liquid substrate materials, such as silicone oils, ionic liquids and vegetable oils, to synthesize metal films and nanoparticles made of gold, silver, titanium, aluminum, iron, nickel and copper via sputtering and thermal evaporation processes [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Besides, the growth of crystals from different aromatic hydrocarbons, zinc, copper and gold on silicone oil and ionic liquids by vapor phase deposition was studied [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the growth of crystals from different aromatic hydrocarbons, zinc, copper and gold on silicone oil and ionic liquids by vapor phase deposition was studied [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. It is unanimously reported that a multi-step formation mechanism occurs when depositing metals on liquids [ 1 , 2 , 3 , 4 , 5 , 7 , 8 , 9 , 10 , 13 , 15 , 16 , 17 , 18 , 19 , 21 , 23 , 24 , 25 , 26 ]. First, nucleation and growth of smaller clusters can be observed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also showed the coercivity behavior of the Fe film and its temperature dependence [ 272 ]. The observation of the Fe thin film morphology deposited by sputtering over silicon oil painted onto a frosted glass surface has been further investigated [ 130 , 141 , 273 ]. The appearance of disk-shaped structures has been reported [ 141 ].…”
Section: Reviewmentioning
confidence: 99%
“…The observation of the Fe thin film morphology deposited by sputtering over silicon oil painted onto a frosted glass surface has been further investigated [ 130 , 141 , 273 ]. The appearance of disk-shaped structures has been reported [ 141 ]. Moreover, the impact of annealing on the microstructure and properties of a Fe thin film has been studied [ 273 ].…”
Section: Reviewmentioning
confidence: 99%